THE AGILITY OF WOMEN ENTREPRENEURS IN HAERHAVE LKP, DEPOK WEST JAVA - Setiawati, Ratna (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
A woman is in charge of LKP (Course and Training Institute) Haerhave, which belongs to the "Haerhave Family" Foundation and operates under a license for "Human Resource Provisioning Professional Certification." In creating their families and nations, Indonesian women are given the same opportunities and respect as males. Due to the equality of obligations, Indonesian women must have a balanced household and public role in addressing global concerns. The study looks at the market knowledge and networking skills of female entrepreneurs around the world, especially during the COVID-19 pandemic. Due to the ban on crowding and the requirement to maintain a safe distance, female business owners must come up with strategies to sustain their enterprises. The discussion literature is drawn from a variety of qualitative research approaches. The practice of switching from offline to online SOP (Operational Standards) training has altered. The findings of this study demonstrate how women’s participation and agility in coaching have an impact on home income and how they care for their trainees like family.